The Effect of the Multiliteracy Learning Model on Critical Thinking Skills in Terms of College Students’ Self-Regulated Learning - Fadhil Purnama Adi; Idam Ragil Widianto Atmojo; Roy Ardiansyah; Milenia Suci Rachmawati (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2023)
As a teacher candidate, a college student should master 21st-century skills. Critical thinking is one of the directions of 21st-century education. As prospective educators, college students also need to master critical thinking skills supported by good self-regulated learning as a provision so that they can carry out meaningful learning in class later. This study aims to analyze the effect of applying the multiliteracy learning model on college students' critical thinking skills in terms of their self-regulated learning. The research method used was a quantitative experiment with a 2 x 3 factorial design. The test instrument employed a two-tier essay with a total of six items, which had been declared valid and reliable. Data analysis was performed after all data from respondents had been collected then continuing hypotheses. Based on the results of testing the hypothesis employing a two-way ANOVA test with different cells, the results obtained were Fobs > Fα, with details of Fa > Fα (18.03901 > 3.986269479), Fb > Fα (27.5862 > 3.135917934), and Fab > Fα (139.2992 > 3.135917934). These results reveal that the multiliteracy learning model affected college students' critical thinking skills, self-regulated learning influenced college students' critical thinking skills, and the multiliteracy learning model interacted with the level of self-regulated learning on critical thinking skills.